Treatment outcome of imported cutaneous leishmaniasis among travelers and migrants infected with Leishmania major and Leishmania tropica: a retrospective study in European centers 2013 to 2019. (September 2022) - Glans, Hedvig; Dotevall, Leif; Van der Auwera, Gert; Bart, Aldert; Blum, Johannes; Buffet, Pierre; Guery, Romain; Gangneux, Jean-Pierre; van Henten, Saskia; Harms, Gundel; Varani, Stefania; Robert-Gangneux, Florence; et al.
Highlights: Cases caused by Leishmania major were mostly infected when visiting friends and relatives. Most cases caused by Leishmania tropica occurred in migrants. Pentavalent antimony had an overall cure rate of 76%, in line with previous studies. The cure rate for intralesional pentavalent antimony was higher (86%) than that for systemic (67%). Liposomal amphotericin B had a cure rate of 44% for cases caused by L. tropica . ABSTRACT: Objectives: Cutaneous leishmaniasis (CL) in Asia, Northern, and Sub-Saharan Africa is mainly caused by Leishmania major and Leishmania tropica . We describe and evaluate the treatment outcome of CL among travelers and migrants in Europe. Methods: We conducted a retrospective study of parasitological confirmed CL cases caused by L. major and L. tropica during 2013-2019 in Europe. Data were collected from medical records and databases within the LeishMan network. Results: Of 206 included cases of CL, 75 were identified as L. major and 131 as L. tropica . Of patients with L. tropica infection, 80% were migrants, whereas 53% of patients with L. major infection had been visiting friends and relatives. Among patients with L. tropica, 48% were younger than 15 years. Pentavalent antimony cured 73% ( L. major ) and 78% ( L. tropica ) of patients. The cure rate for intralesional administration was 86% and 67% for systemic, on L. tropica . Liposomal amphotericin B had a cure rate of 44-63%. Conclusion: L. major infections were mostly found in individuals visiting friends and relatives, whereas L. tropica were mainly identified in migrants. No patients with L. major relapsed. Pentavalent antimony, liposomal amphotericin B, and cryotherapy had cure rates in accordance with previous studies.